Evil in the Lord of the Rings an application of Tolkien's Mythopoeia - Koo, Crystal Gail S. (College of Arts and Letters, University of the Philippines Diliman, 2005)
This thesis examines the theme of evil in J.R.R. Tolkien's The Lord of the Rings, an essential principle in the plot and meaning of the trilogy. I seek to establish the interpretation that the trilogy's portrayal of evil is an application of Tolkien's theory of myhtopoeia. His theory asserts that a myth must be constructed by the elements of the Primary of the Real World, in which Christian truths are vital; The Lord of the Rings is such a myth in that its portrayal of evil is drawn and sub-created from the orthodox Christian view of evil. The definition and origin of evil as propounded by St. Augustine is parallel consistently in The Lord of the Rings through the case histories of its primary evil figures. The characteristics of evil that St. Augustine asserts are also translated in the appearance, behavior, and actions of the evil figures in the trilogy. In addition, the element of the fantastic contributes in making the nature of evil as declared by St. Augustine immediately and visibly perceived by the reader.